Effect of dimethylaminohexadecyl methacrylate mass fraction on fracture toughness and antibacterial properties of CaP nanocomposite. Issue 12 (December 2015) - Wu, Junling; Zhou, Han; Weir, Michael D.; Melo, Mary Anne S.; Levine, Eric D.; Xu, Hockin H.K.
Abstract: Objectives: Biofilm acids contribute to secondary caries which is a reason for restoration failure. Previous studies synthesized nanoparticles of amorphous calcium phosphate (NACP) and dimethylaminohexadecyl methacrylate (DMAHDM). The objectives of this study were to develop DMAHMD-NACP nanocomposite for double benefits of antibacterial and remineralization capabilities, and investigate the DMAHMD mass fraction effects on fracture toughness and biofilm response of NACP nanocomposite for the first time. Methods: DMAHDM was incorporated into NACP nanocomposite at mass fractions of 0% (control), 0.75%, 1.5%, 2.25% and 3%. A single edge V-notched beam method was used to measure fracture toughness K IC . A dental plaque microcosm biofilm model using human saliva as inoculum was used to measure the antibacterial properties of composites. Results: K IC was about 1 MPa × m 1/2 for all composite (mean ± sd; n  = 6). Adding DMAHDM from 0% to 3% did not affect K IC ( p  > 0.1). Lactic acid production by biofilms on composite containing 3% DMAHDM was reduced to less than 1% of that on composite control. Metabolic activity of adherent biofilms on composite containing 3% DMAHDM was reduced to 4% of that on composite control. Biofilm colony-forming unit (CFU) counts were reduced by three orders of magnitude on NACP nanocomposite containing 3% DMAHDM. Conclusions: DMAHDM-NACP nanocomposite had good fracture resistance, strong antibacterial potency, and NACP for remineralization (shown in previous studies). The DMAHDM-NACP nanocomposite may be promising for caries-inhibiting dental restorations, and the method of using double agents (DMAHDM and NACP) may have a wide applicability to other dental materials including bonding agents and cements.